(untitled) (Research, Society and Development, 2021)
It is known that plants have acquired and adapted tolerance mechanisms, such as: more extensive root system and greater root/shoot ratio, changes in stomatal frequency behavior, thicker leaf cuticle, changes in leaf angle, accumulation of metabolites, osmotic adjustment and resistance to cell dehydration. These adaptive modifications can be specific to each genotype, and involve several mechanisms that can be efficient in water use. Thus, the objective of the present work was to show that root phenotyping techniques have been shown to be the most efficient driving tools of selection for drought tolerance in corn. For this, works from the SciELO database, Google Scholar, academic articles and published books were used, relevant to the topic in question. And based on these studies, it was possible to understand that the acquisition of water and nutrients by the root system and its capacity to exploit the soil, form the basis for plant development, being a response factor for the beginning of development, and determinant for the grains yield. Furthermore, with root phenotyping there are selection advantages through one more criterion, other than field phenotyping. Thus, it is possible to admit a saving of time and financial investment, in addition to the development of technology with the validation of root phenotyping.